Rancang Bangun Prototype Sistem Kontrol Kunci Pintu Berbasis Suara Arduino Uno - Safutra, Edo; Hidayat, kemas Muhammad Wahyu; Perdana, Meiylana Winda (Jurnal Nasional Ilmu Komputer, 2024)
Information Technology is a technology used to manage Data, including processing, obtaining, compiling, storing, and manipulating data in various ways to produce quality information, namely relevant, accurate, and timely information; the development of Information Technology continues at a rapid pace, and its impact is felt in almost all aspects of our lives. These changes affect how we work, learn, play, and communicate, and they continue to open the door to innovations and greater changes in the future. This study aims to develop a more practical, innovative door lock system through voice recognition technology. Using Arduino Uno as the main microcontroller, this system can automatically recognize specific voice commands to operate the door lock. Integrating hardware and software allows users to control the door lock simply by saying pre-programmed command words. The results of the study indicate that this system has the potential to be a more user-friendly alternative compared to conventional lock systems. Furthermore, this system can be further developed by adding additional security features such as biometric verification or integration with smart home systems.